a) 2(x-y)(x+y)+(x-y)2+(x+y)2
b) (x-y+z)2+(z-y)2+2(x-y+z)(y-z)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
2: Ta có: \(x^4-3x^3-24x+8\)
\(=x^3\left(x-3\right)-8\left(x-3\right)\)
\(=\left(x-3\right)\left(x-2\right)\left(x^2+2x+4\right)\)
a) 2(x-y)(x+y)+(x-y)2+(x+y)2
=2x2-2y2+x2-2xy+y2+x2+2xy+y2
=(2x2+x2+x2)+(2xy-2xy)+(-2y2+y2+y2)
=4x2
b) (x-y+z)2+(z-y)2+2(x-y+z)(y-z)
=x2+y2+z2-2xy-2yz+2zx+xy-zx+2yz-y2-z2
=x2+(y2-y2)+(z2-z2)+(xy-2xy)+(2yz-2yz)+(2xz-xz)
=x2-xy+zx
a) \(2\left(x-y\right)\left(x+y\right)+\left(x-y\right)^2+\left(x+y\right)^2\)
\(=2\left(x-y\right)\left(x+y\right)+\left(x-y+x+y\right)^2-2\left(x-y\right)\left(x+y\right)\)
\(=\left(x-y+x+y\right)^2\)
\(=\left(2x\right)^2=4x^2\)
b) \(\left(x-y+z\right)^2+\left(z-y\right)^2+2\left(x-y+z\right)\left(y-z\right)\)
\(=\left(x-y+z+y-z\right)^2-2\left(x-y+z\right)\left(y-z\right)+2\left(x-y+z\right)\left(y-z\right)\)
\(=x^2\)